Closed subgroups of a quadratic form scheme - Krawczyk, Grzegorz (Annales Mathematicae Silesianae, 1990)
In the paper the number c(S) of closed subgroups of a quadratic form scheme S is considered. We determine c(S) for some classes of schemes. Schemes with small c(S) are characterized and the behaviour of c(S) under known operation on schemes are discussed, as well.